Optical Fiber Communication Conference (OFC) 2020 2020
DOI: 10.1364/ofc.2020.th1f.1
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of Anomaly Points and Fiber types in Multi-span Transmission Links Only by Receiver-side Digital Signal Processing

Abstract: We experimentally demonstrate simultaneous localization of optical excess loss points and spans with different dispersion in multi-span fiber links using a neural-network based digital backpropagation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 2 publications
1
22
0
Order By: Relevance
“…This paper is an invited extension of our work presented in [20], where an optical fiber power profile and individual frequency responses of multiple optical filters were successfully obtained. This study extends [20] and our previous works [19] [21] [22] from the following perspectives:…”
supporting
confidence: 88%
See 1 more Smart Citation
“…This paper is an invited extension of our work presented in [20], where an optical fiber power profile and individual frequency responses of multiple optical filters were successfully obtained. This study extends [20] and our previous works [19] [21] [22] from the following perspectives:…”
supporting
confidence: 88%
“…Accordingly, Tanimura et al have demonstrated the signal power (loss) profile extraction of a 260km multi-span link from only received signals using a correlation method (CM) [18]. Our previous studies and other groups [19]- [23] have shown that not only the power profile but also CD maps, amplifiers' gain spectra, and the passband narrowing (PBN) at optical filters can be estimated. Since these methods reveal optical components' characteristics in the fiber propagation direction with digital signal processing (DSP), we call these techniques digital longitudinal monitoring (DLM) here.…”
mentioning
confidence: 99%
“…Adagrad [17] and Adam [18]); (iv) simultaneous optimization of nonlinear and linear coefficients enables discriminative measurement of the linear responses before and after the nonlinearity (and vice versa) at once due to the non-commutativity of nonlinear and linear phenomena. Similar ideas can be seen in the context of fiber nonlinearity compensation [19] and the estimation of longitudinal fiber loss and dispersion profiles [20].…”
Section: Introductionmentioning
confidence: 62%
“…If the estimation is not simultaneous such as small-signal measurement and low-frequency measurement [7], the estimated responses will be the combined version of each response and not be separated. As a different example of distinguishing cascaded linear response, the estimation of fiber nonlinearity and dispersion (linear response) profile along the transmission fiber has successfully demonstrated in [20] on the basis of the simultaneous learning of the nonlinear and linear coefficients in nonlinear Schrödinger equation, which is also composed of concatenated nonlinear and linear operations.…”
Section: Learning Algorithmmentioning
confidence: 99%
“…In this method, characteristic information of optical signals is collected from a digital signal processor (DSP) and other optical devices in the receiving end transponders. Some similar methods utilize the signal-to-noise ratio (SNR) with estimations of end-to-end optical channels using machine learning or an analytical model such as Gaussian noise to localize anomalies [3][4] or utilize nonlinear and dispersion coefficients using digital backpropagation to localize optical excess loss points [5]. The proposed method can be potentially used to cover a wide range of failure patterns that may occur in the optical transport network by utilizing various parameters.…”
Section: Introductionmentioning
confidence: 99%